Maximally effective dosing regimens of meropenem in patients with septic shock. (12th September 2017) - Sjövall, Fredrik; Alobaid, Abdulaziz S; Wallis, Steven C; Perner, Anders; Lipman, Jeffrey; Roberts, Jason A
Abstract: Objectives: To use a population pharmacokinetic approach to define maximally effective meropenem dosing recommendations for treatment of Acinetobacter baumannii and Pseudomonas aeruginosa infections in a large cohort of patients with septic shock. Methods: Adult patients with septic shock and conserved renal function, treated with meropenem, were eligible for inclusion. Seven blood samples were collected during a single dosing interval and meropenem concentrations were measured by a validated HPLC-MS/MS method. Monte Carlo simulations were employed to define optimum dosing regimens for treatment of empirical or targeted therapy of A. baumannii and P. aeruginosa . EudraCT-no. 2014-002555-26 and NCT02240277. Results: Fifty patients were included, 26 male and 24 female, with a median age of 64 years with an all-cause 90 day mortality of 34%. A two-compartment linear model including creatinine clearance (CLCR ) as a covariate best described meropenem pharmacokinetics. For empirical treatment of A. baumannii, 2000 mg/6 h was required by intermittent (30 min) or prolonged (3 h) infusion, whereas 6000 mg/day was required with continuous infusion. For P. aeruginosa, 2000 mg/8 h or 1000 mg/6 h was required for both empirical and targeted treatment. In patients with a CLCR of ≤ 100 mL/min, successful concentration targets could be reached with intermittent dosing of 1000 mg/8 h. Conclusions: In patients with septic shock and possible augmented renal clearance, doses should be increased and/or administration should be performed by prolonged or continuous infusion to increase the likelihood of achieving therapeutic drug concentrations. In patients with normal renal function, however, standard dosing seems to be sufficient.